Botulinum toxin type A injections for masticatory muscles hypertrophy: A systematic review. Issue 1 (January 2022) - Rauso, Raffaele; Lo Giudice, Giorgio; Tartaro, Gianpaolo; Zerbinati, Nicola; Nicoletti, Giovanni Francesco; Fragola, Romolo
Abstract: The aim of this study is to compare the efficacy of single-point injection of botulinum toxin A versus multi-point operative protocols found in the literature in reducing hypertrophy in patients with masticatory muscle hypertrophy. A systematic review was performed in accordance with the Park et al., 2018 guidelines, selecting articles from PubMed, Google Scholar, Web of Science and Ovid databases up to July 8, 2020.28 studies met the eligibility criteria. 748 patients were treated for masseter hypertrophy (MH) and 4 patients for temporal muscle hypertrophy. As for MH: in 45.2% of cases 3 injection sites (IS) were used, in 18.8% 1 IS, in 16.2% 2 IS, in 13% 5 IS, in 4.1% 6 IS, 2.7% 4 IS. At three months, the mean reduction in masseter muscle thickness is 26–31% when 1 IS was used, 28% in 2 IS, 12–27% in 3 IS and 22–30% in 6 IS. Heterogeneity of results, high bias level and selective reports led to a difficult efficacy comparison of the injection techniques described. Data suggest that the lowest number of IS possible should be used until stronger evidences are presented. Homogeneity in pre- and post-operative protocols is needed to establish a reliable setting for the condition under study.